A construção da identidade das editoras pelas 1ªs capas: Record e Cosac Naify - Fraga, Claudia Trevisan (2008)
This research intends to study the Brazilian publishers identity construction based on its books front cover. Our proposition searched to recognize the common and distinctive procedures used specifically on its first front covers. Considering the great number of publishers present in the Brazilian market we have chosen an initial clipping, which caused the selection of two among the seven biggest publishers in expansion. It refers to Record, considered the oldest and Cosac Naify, the newest. In a second moment, we considered these two publishers actuation during 2007, and we selected for analysis the fiction segment according to the ranking of the five best sellers. From a corpus of five fiction front covers, we elected randomly three first front cover a for each publisher as a sample of its suitable operation. In this investigation the first front cover is taken not only as a package but also as both the book and the publisher identitary face. For the designers that create it, it is developed and treated like an advertisement which sells products based on the first contact between the book and the consumer. Calling into question this kind of interaction as meaning production and publishers identity construction, we examine what is the articulation among verbal, visual and spacial systems expression function in the first front cover, and how these kind of articulation edify the identity´s expression. Approaching the distinctive kinds of visibility that the two publishers sincretic articulation create on its first front covers we conclude that, beyond the strategy of an enunciator/publisher that makes the enunciatary/reader makes sense of the book, it also infers that the publishers use the making feel thought through a combination of sensitive attributes of the first front cover constituent elements as a whole sense. These two designator s ways of doing have been approached in the E. Landowski sociossemiotic as two kinds of interaction: manipulation and adjustment. The discursive semiotic and its model of meaning analysis based on content plane developed around A.J.Greimas, as well as the visual semiotic with the contributions of J.M. Floch based the procedures of description and analysis of the visual texts. For the sensible and intelligible experiences that these texts produce, our approach founded its basis in E. Landowski to develop them as persuasive strategies and as lived experiences, both occurring in distincts kinds of interaction between communication actants. In the first case, processing the ready made signification of the front cover. In the second one, processing the meaning in act. These two interactive procedures led us also to conclude about the two kinds of specification that define the readers, which oriented us to understand the publishers identity construction. Alongside A. C. de Oliveira we concluded that, besides the content plane arrangement, the expressive articulation procedures adopted by the publishers are also the basis of the two distinctive procedures of identity construction: by quantity and by qualification